Learning from each other: The multifaceted potential for partnership between the Republic of Korea and Germany - Niels Keijzer; Stephan Klingebiel; Min Jee Oh (German Institute of Development and Sustainability (IDOS), 2022)
Although geographically distant, there is considerable convergence in the development policy priorities of Germany and the Republic of Korea (hereafter: Korea) - and indeed scope for cooperation between them. Whereas Germany was a founding member of the international development cooperation system as we know it today, Korea is a recent member of the Organisation for Economic Co-operation and Development (OECD) and its Development Assistance Committee (DAC) and both an important former recipient as well as a current provider of development cooperation. The development policies and operations of Germany and Korea are confronted by a challenging global geopolitical and economic setting, as well as a worrying decline in human development globally. Both countries are being challenged to respond to this changing setting and to communicate such changes effectively in their contributions towards advancing sustainable development at home and through international cooperation. Both countries have seen considerable increases in their official development assistance (ODA) budgets during the past decade, with Korea expected to continue its gradual growth path, whereas Germany may face challenges to consolidate its ODA budget - notwithstanding its important position as the only G7 member that has reached the target of providing 0.7 per cent of its gross national income (GNI) as ODA. This policy brief describes and discusses the German and Korean systems for setting development policy. Both countries maintain a centralised political respon- sibility for development policy - in Germany's case with a dedicated ministry, whereas in Korea, two ministries share the responsibility for development cooperation. With various line ministries and organisations with implementing mandates involved in both countries' development cooperation systems, fragmentation is a challenge and raises questions about issues that include results reporting, the introduction and use of standard indicators, independent evaluations, con- sistent ODA reporting and ensuring effective cooperation. Based on the exploration of the countries' respective systems and policy priorities, we recommend a regular horizontal dialogue on common operational interests. In addition, we identify scope for enhanced cooperation in three substantive areas, which in turn may serve to identify further horizontal dialogue, these being: strengthening the multilateral system, as well as supporting complementary initiatives that promote the involvement of non-state actors in realising the 2030 Agenda, global health, specifically the provision of medication - including vaccination - as a global public good, and the green energy transition, with both countries being committed to increasing climate finance.
Keywords: 320; German and European and multilateral development policy